2021
DOI: 10.1620/tjem.253.241
|View full text |Cite
|
Sign up to set email alerts
|

Extended-Hours Hemodialysis without Dietary Restrictions Is Associated with Lower Risk for Developing of Dialysis-Related Amyloidosis

Abstract: Dialysis-related amyloidosis (DRA) is characterized by the deposition of amyloid consisting of beta2microglobulin in the musculoskeletal system, causing carpal tunnel syndrome, destructive spondyloarthropathy, and/or bone cysts. Increased cystic radiolucency of the bones and tendon thickening due to inflammation are common findings in DRA. We have developed a new dialysis method, extendedhours hemodialysis without dietary restrictions for the aim of improving both hypertension and malnutrition. We retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…After extended-hours hemodialysis without dietary restrictions, patients with increased or maintained BMI had a lower risk of death (Hishida et al 2020). In addition, Tabata et al (2021) also reported a decreased risk of developing dialysis amyloidosis. Therefore, starting extended-hours hemodialysis early in the induction of dialysis (younger age) may reduce the risk of various complications.…”
Section: Accepted Manuscript 13mentioning
confidence: 96%
“…After extended-hours hemodialysis without dietary restrictions, patients with increased or maintained BMI had a lower risk of death (Hishida et al 2020). In addition, Tabata et al (2021) also reported a decreased risk of developing dialysis amyloidosis. Therefore, starting extended-hours hemodialysis early in the induction of dialysis (younger age) may reduce the risk of various complications.…”
Section: Accepted Manuscript 13mentioning
confidence: 96%